Implementation of the Law on Sexual Violence: Challenges in Case Handling and Law Enforcement - Oktaviani Siswati, Ceria; Sunggara, Muhamad Adystia (Dinasti Research, 2025)
The enactment of the Law on the Elimination of Sexual Violence represents a significant milestone in addressing sexual violence in society. This study examines the challenges and progress in implementing the Law on Sexual Violence Crimes, particularly in handling cases and ensuring effective law enforcement. Using a qualitative approach, data were gathered from legal documents and case studies. Findings indicate that while the Law on Sexual Violence Crimes has improved victim protection and provided a clearer legal framework, challenges persist in social stigma, lack of legal awareness, and resource constraints among law enforcement agencies. Additionally, inconsistencies in judicial interpretations and procedural delays hinder the effective resolution of cases. Recommendations include strengthening inter-agency coordination, increasing public awareness campaigns, and ensuring adequate training for law enforcement and judiciary personnel to enhance sensitivity and professionalism in handling sexual violence cases. This study underscores the importance of a multi-sectoral approach to ensure justice for victims and uphold the principles of the Law on Sexual Violence Crimes.